Agriculture and climate change in national green growth strategies - Negra, Christine (2013)
As a national development model that simultaneously pursues socio-economic progress and environmental conservation, the Green Growth concept is being tested in countries around the world through context-specific policies and projects. This report reviews Green Growth policy actions related to agriculture and climate change by eight countries – Mexico, Vietnam, Rwanda, India, South Korea, China, France and Australia – and assesses progress and challenges as well as the apparent significance of the 2007-2008 global financial crisis in motivating Green Growth strategies. As national strategies evolve into on-the-ground practice, robust investment in climate-smart agriculture will be essential to achieving real sustainability.